2022
DOI: 10.3390/toxics10090497
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) Exposure Triggers Inflammation and Endothelial Dysfunction in BALB/c Mice: A Pilot Study

Abstract: The particulate matter present in air pollution is a complex mixture of solid and liquid particles that vary in size, origin, and composition, among which are polycyclic aromatic hydrocarbons (PAHs). Although exposure to PAHs has become an important risk factor for cardiovascular disease, the mechanisms by which these compounds contribute to increased cardiovascular risk have not been fully explored. The aim of the present study was to evaluate the effects of PAH exposure on systemic pro-inflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In a preclinical study, Rojas et al 163 noted that a single exposure to a mixture of PAHs similar to those found in WFS significantly elevated plasma concentration of IL-6, IL-1β, TNF-α, and IFN-γ in male BALB/c mice. Analysis of aortic tissues further revealed transcriptomic upregulation of genes associated with endothelial dysfunction ( Vcam1 , Icam1 , and Sele ) and reduction-oxidation imbalance, consistent with the accumulation of adhesion molecules ICAM-1 and VCAM-1.…”
Section: Mechanistic Insightsmentioning
confidence: 76%
See 1 more Smart Citation
“…In a preclinical study, Rojas et al 163 noted that a single exposure to a mixture of PAHs similar to those found in WFS significantly elevated plasma concentration of IL-6, IL-1β, TNF-α, and IFN-γ in male BALB/c mice. Analysis of aortic tissues further revealed transcriptomic upregulation of genes associated with endothelial dysfunction ( Vcam1 , Icam1 , and Sele ) and reduction-oxidation imbalance, consistent with the accumulation of adhesion molecules ICAM-1 and VCAM-1.…”
Section: Mechanistic Insightsmentioning
confidence: 76%
“…Analysis of aortic tissues further revealed transcriptomic upregulation of genes associated with endothelial dysfunction ( Vcam1 , Icam1 , and Sele ) and reduction-oxidation imbalance, consistent with the accumulation of adhesion molecules ICAM-1 and VCAM-1. 163 Finally, Robertson et al 164 reported that a single, 4-hour-long O 3 exposure at 1 ppm concentration promoted lung inflammation and attenuated the acetylcholine-mediated vasodilatation of isolated aortas from female C57BL/6 but not CD36 −/− mice, compared with filtered air. The latter, however, was recapitulated in naïve isolated aortas from female C57BL/6 mice following treatment with serum from O 3 -exposed mice of both genotypes.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…The cardiovascular toxicity of PAHs was validated by several studies based on experiment. Studies determined that PAH exposure on mice and humans could cause oxidative, inflammation, lipid dysfunction, and endothelial dysfunction, which were linked to higher systolic blood pressure and heart rate variability. Despite these, evidence displayed that an epigenetic factor such as DNA methylation could be disturbed by PAHs exposure and dysregulate the downstream gene expression, which may also help explain the complex effects on PAHs exposure on cardiovascular disease …”
Section: Discussionmentioning
confidence: 99%
“…A study of nasal drops of PAHs in BALB/ c mice found that PAHs such as phenanthrene, fluoranthene, and pyrene caused inflammation and endothelial dysfunction in the mice. 154 Endothelial dysfunction is an important cause of several cardiovascular diseases, including atherosclerosis. Some in vitro studies have shown that PAHs, NPAHs, and OPAHs can cause endothelial dysfunction.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Toxicological studies reached the same conclusion. A study of nasal drops of PAHs in BALB/c mice found that PAHs such as phenanthrene, fluoranthene, and pyrene caused inflammation and endothelial dysfunction in the mice . Endothelial dysfunction is an important cause of several cardiovascular diseases, including atherosclerosis.…”
Section: The Health Impact Of Pah Derivatives On Humans and Animalsmentioning
confidence: 99%